Biologia - Czechowski, Wojciech; Gajewski, Waclaw; Krzysztoforski, Andrzej; Karabin, Andrzej (Warszawa : Panstwowe Wydawn. Rolnicze i Lesne, 1989)
An introductory encyclopedia of Biology.
Keywords: Biology